Adherence to colonoscopy in cascade screening of colorectal cancer: A systematic review and meta‐analysis. Issue 4 (3rd January 2022) - Wu, Weimiao; Huang, Junjie; Yang, Yihui; Gu, Kai; Luu, Hung N; Tan, Songsong; Yang, Chen; Fu, Jiongxing; Bao, Pingping; Ying, Tao; Withers, Mellissa; Mao, Dandan; et al.
Abstract: Background and Aim: This study aims to systematically evaluate adherence to colonoscopy and related factors in cascade screening of colorectal cancer (CRC) among average‐risk populations, which is crucial to achieve the effectiveness of CRC screening. Methods: We searched PubMed, Embase, Web of Science, and Cochrane Library for studies published in English up to October 16, 2020, and reporting the adherence to colonoscopy following positive results of initial screening tests. A random‐effects meta‐analysis was applied to estimate pooled adherence and 95% confidence intervals. Subgroup analysis and mixed‐effects meta‐regression analysis were performed to evaluate heterogeneous factors for adherence level. Results: A total of 245 observational and 97 experimental studies were included and generated a pooled adherence to colonoscopy of 76.6% (95% confidence interval: 74.1–78.9) and 80.4% (95% confidence interval: 77.2–83.1), respectively. The adherence varied substantially by calendar year of screening, continents, CRC incidence, socioeconomic status, recruitment methods, and type of initial screening tests, with the initial tests as the most modifiable heterogeneous factor for adherence across both observational ( Q = 162.6, P < 0.001) and experimental studies ( Q = 23.2, P < 0.001). The adherence to colonoscopy was at the highest level when using flexible sigmoidoscopy as an initial test, followed by using guaiac fecal occult blood test, quantitative or qualitative fecal immunochemical test, and risk assessment. The pooled estimate of adherence was positively associated with specificity and positive predictive value of initial screening tests, but negatively with sensitivity and positivity rate. Conclusions: Colonoscopy adherence is at a low level and differs by study‐level characteristics of programs and populations. Initial screening tests with high specificity or positive predictive value may be followed by a high adherence to colonoscopy.